Early weight gain influences duration of breast feeding: prospective cohort study. Issue 11 (15th July 2022) - Olga, Laurentya; van Diepen, Janna A; Gross, Gabriele; Dunger, David B; Ong, Ken K
Abstract : Objective: While several studies have shown that milk formula feeding is associated with faster infant weight gain compared with exclusively breast feeding (EBF), we explored the possible reverse association that infant weight gain influences the duration of EBF. Design: Prospective birth cohort study (Cambridge Baby Growth Breastfeeding Study) born 2015–2018. Setting: Cambridge, UK. Participants: Full-term, singleton, normal birthweight infants who received EBF for 2–5 completed weeks (n=54), 6–11 weeks (n=14) or 12 or more weeks (n=80). Intervention: Weight gain from birth to 2 and 6 weeks. Main outcome and measure: Duration of EBF. Results: Faster infant weight gain during EBF predicted longer duration of EBF. Among all 148 infants, each +1 unit gain in weight SD score (SDS) between birth and 2 weeks (while all infants received EBF) reduced the likelihood of stopping EBF between 2 and 5 weeks by ~70% (OR 0.32; 95% CI 0.12 to 0.77; adjusted for sex, gestational age at birth, birth weight and mother's age, prepregnancy BMI and education). Similarly, among infants EBF for 6 or more weeks (n=94), each +1 unit gain in weight SDS between birth and 6 weeks reduced the likelihood of stopping EBF between 6 and 11 weeks by ~80% (OR 0.18; 95% CI 0.05 to 0.63). Conclusions: Slower early infant weight gain was consistently associated with subsequent earlier discontinuation of EBF. We conjecture that broader recognition of the wide range of normal infant growth might encourage parents to not stop EBF earlier than they intended. Abstract : In this longitudinal cohort study of term, singleton, normal birthweight, initially exclusively breastfed infants, slower weight gain while exclusively breast feeding was associated with higher likelihood of introduction of infant milk formula in subsequent follow-up periods, between 2 and 11 weeks.